Exploring the entrepreneurial behavior of vegetable growers: influential factors and implications for agricultural development - Niyati Thakur; Ravinder Sharma; Pankaj Thakur; Shilpa; Ashutosh Chaturvedi; Richa Khushwaha; Saswat Kumar Pani; Vijay Kumar Yadav; Akash Gaurav Singh; Ajit Sharma; Prashant Sharma (Frontiers in Sustainable Food Systems)
IntroductionEntrepreneurship in agricultural sector is a key enabler of rural development and economic growth. This research delves into the entrepreneurial behavior of vegetable growers involved in polyhouse protected farming and focuses on the factors that influence their entrepreneurial pursuits.MethodsThe research employed a mixed sampling methodology and the data collection was done by personally interviews. Whereas, data were analyzed using various statistical techniques including Entrepreneurial behavior index computation and Kendall’s tau correlation.ResultsThe results of the study reveal noteworthy associations between factors such as farm income, experience in protected cultivation, area allocated for polyhouse cultivation and extension contact with entrepreneurial behavior. Notably, income consistently demonstrated a positive correlation with all aspects of entrepreneurial behavior, while experience and extension contact also exhibited significant positive relationships. Conversely, education level displayed a negative correlation with risk-taking ability but a positive correlation with other dimensions such as cosmopoliteness and innovativeness. However, family size and gender did not demonstrate significant associations with entrepreneurial behavior.DiscussionThe findings underscored the intricate nature of entrepreneurial behavior among vegetable growers which necessitate tailored interventions to foster entrepreneurship in this sector. The research recommends policy measures like financial incentives, enhanced access to extension services and promoting collaboration among polyhouse cultivators to encourage entrepreneurship. These initiatives aim to overcome financial barriers, improve technical knowledge and address structural challenges, ultimately fostering sustainable entrepreneurship and agricultural development.